Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/s0928-8244(03)00302-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anthrax infection with combination of ciprofloxacin and antibodies to protective antigen ofBacillus anthracis

Abstract: Currently there is no effective treatment for inhalational anthrax beyond administration of antibiotics shortly after exposure. There is need for new, safe and effective treatments to supplement traditional antibiotic therapy. Our study was based on the premise that simultaneous inhibition of lethal toxin action with antibodies and blocking of bacterial growth by antibiotics will be beneficial for the treatment of anthrax. In this study, we tested the effects of a combination treatment using purified rabbit or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…Although naturally occurring anthrax infection of humans is rare, the 2001 anthrax attack through the US Postal Service highlighted the need for a safe and efficacious postexposure therapy for anthrax infection. The current Centers for Disease Control recommendations for treatment following potential exposure to aerosolized B. anthracis spores calls for administration of antibiotics for at least 60 d and the licensed protective antigen-based vaccine (1). However, antibiotic treatment can be ineffective when bacterial strains are antibiotic resistant (2).…”
mentioning
confidence: 99%
“…Although naturally occurring anthrax infection of humans is rare, the 2001 anthrax attack through the US Postal Service highlighted the need for a safe and efficacious postexposure therapy for anthrax infection. The current Centers for Disease Control recommendations for treatment following potential exposure to aerosolized B. anthracis spores calls for administration of antibiotics for at least 60 d and the licensed protective antigen-based vaccine (1). However, antibiotic treatment can be ineffective when bacterial strains are antibiotic resistant (2).…”
mentioning
confidence: 99%
“…If antibiotics are applied at this stage, the infection can still be lethal because of the accumulation of the toxins. Logically, an effective therapeutic approach would include simultaneous blocking of bacterial growth by antibiotics and neutralization of anthrax toxin with antitoxins (2)(3)(4)(5). Extensive research efforts both before and after the anthrax attacks of 2001 have made anthrax toxin one of the best-understood channel-facilitated protein translocation systems (refs.…”
mentioning
confidence: 99%
“…Moreover it has been shown that the combination of toxin neutralization with antibodies and inhibition of bacterial growth by antibiotics is very effective in a small animal anthrax challenge model [14]. Antianthrax toxin antibodies, which neutralize the immunosuppressive effects of PA/LF/EF, working in concert with conventional antibiotics may provide additional protection in the event of an anthrax spore exposure.…”
Section: Introductionmentioning
confidence: 99%